Co‐occurrence of bobcats, coyotes, and ocelots in Texas. Issue 11 (21st April 2020) - Lombardi, Jason V.; MacKenzie, Darryl I.; Tewes, Michael E.; Perotto‐Baldivieso, Humberto L.; Mata, José M.; Campbell, Tyler A.
Abstract: Interspecific competition among carnivores has been linked to differences in behavior, morphology, and resource use. Insights into these interactions can enhance understanding of local ecological processes that can have impacts on the recovery of endangered species, such as the ocelot ( Leopardus pardalis ). Ocelots, bobcats ( Lynx rufus ), and coyotes ( Canis latrans ) share a small geographic range overlap from South Texas to south‐central Mexico but relationships among the three are poorly understood. From May 2011 to March 2018, we conducted a camera trap study to examine co‐occurrence patterns among ocelots, bobcats, and coyotes on the East Foundation's El Sauz Ranch in South Texas. We used a novel multiseason extension to multispecies occupancy models with ≥2 interacting species to conduct an exploratory analysis to examine interspecific interactions and examine the potential effects of patch‐level and landscape‐level metrics relative to the occurrence of these carnivores. We found strong evidence of seasonal mutual coexistence among all three species and observed a species‐specific seasonal trend in detection. Seasonal coexistence patterns were also explained by increasing distance from a high‐speed roadway. However, these results have important ecological implications for planning ocelot recovery in the rangelands of South Texas. This study suggests a coexistence among ocelots, bobcats, and coyotes under the environmental conditions on the El Sauz Ranch. Further research would provide a better understanding of the ecological mechanisms that facilitate coexistence within this community. As road networks in the region expand over the next few decades, large private working ranches will be needed to provide important habitat for ocelots and other carnivore species. Abstract : This study aimed to use a novel multiseason extension to multispecies occupancy models with ≥2 interacting species to explore how ocelots, bobcats, and coyotes may potentially behave with one another (e.g., co‐existence/avoidance) and potential effects of landscape factors in the co‐occurrence of the focal species. Our study suggests a strong positive association among the focal species indicating coexistence at the temporal scale of this study. Our study has shown these mutual interactions may also have implications for planning ocelot recovery strategies in the rangelands in southern Texas.